THE USE OF PICTURE AND PICTURE LEARNING MODEL IN IMPROVING LEARNING OUTCOME OF V-GRADE STUDENTS OF SDN TURISKAIN (DURING PANDEMIC) IN SCIENCE COURSES - Heriardus Riu Bere (PROGRES PENDIDIKAN, 2022)
uring this pandemic, educational efforts must still be carried out. The Belu Regency Government has taken a policy to carry out learning activities, namely Learning from Home, this encourages educators to be creative in creating an interesting learning atmosphere. Therefore, this research was conducted using the picture and picture learning model with the aim of increasing the absorption of students' understanding of science subjects. This study uses the Classroom Action Research method. The research implementation is divided into two (II) cycles. The results obtained in the first cycle showed that the average understanding of students who took part in science learning with the picture and picture model, completely reached the KKM (Minimum Completeness Criteria) was only 37.5%, increased in the second cycle by 87.5%. The picture and picture learning model is effective in improving the learning outcomes of fifth grade students at SDN Turiskain during this distance learning period or Learning From Home.